Chronic PPARγ Stimulation Shifts Amyloidosis to Higher Fibrillarity but Improves Cognition - Blume, Tanja; Deussing, Maximilian; Biechele, Gloria; Peters, Finn; Zott, Benedikt; Schmidt, Claudio; Franzmeier, Nicolai; Wind, Karin; Eckenweber, Florian; Sacher, Christian; Shi, Yuan; Ochs, Katharina; et al. (Frontiers in Aging Neuroscience, 2022)
We performed longitudinal β-amyloid positron emission tomography (Aβ-PET) imaging as a translational tool for monitoring of chronic treatment with the peroxisome proliferator-activated receptor gamma (PPARγ) agonist pioglitazone in Aβ model mice. We thus tested the hypothesis this treatment would rescue from increases of the Aβ-PET signal while promoting spatial learning and preservation of synaptic density. Here, we investigated longitudinally for five months PS2APP mice (N=23; baseline age: 8 months) and AppNL-G-F mice (N=37; baseline age: 5 months) using Aβ-PET. Groups of mice were treated with pioglitazone or vehicle during the follow-up interval. We tested spatial memory performance and confirmed terminal PET findings by immunohistochemical and biochemistry analyses. Surprisingly, Aβ-PET and immunohistochemistry revealed a shift towards higher fibrillary composition of Aβ-plaques during chronic pioglitazone treatment. Nonetheless, synaptic density and spatial learning were improved in transgenic mice with pioglitazone treatment, in association with the increased plaque fibrillarity. These translational data suggest that a shift towards higher plaque fibrillarity protects cognitive function and brain integrity. Increases in the Aβ-PET signal upon immunomodulatory treatments targeting Aβ aggregation can thus be protective.